Enhancing The Role of Business in Transferring Research Results into Agriculture: Case Study in Moc Chau District, Son La Province - Ngo, Thi Phuong Quy (H. : ĐHQGHN, 2020)
In recent years, Vietnam’s agriculture has developed strongly thanks to the application of scientific and technological advances in production. Business is a key factor in attracting investment, expanding markets for agricultural products, and an important focal point for transferring research results into agriculture. Based on the assessment of the status of transferring research results into agriculture in Moc Chau district, Son La province over the past time, the paper proposes views and solutions to enhance the role of business in promoting the transfer of research results in local agriculture such as tax favors for business, linkages between business and researchers and enhance the quality of human resources.